Evidance Based Practice Gangguan Persepsi Sensori: Halusinasi Pendengaran Dengan Penerapan Art Therapy - Kaengke, Angelina Prisilia Thereza; Molintao, Winarsi (Yayasan Syalom Cipta Sumikolah, 2025)
Mental disorders are health problems caused by biological, social, psychological, genetic, physical or chemical disorders with the number of sufferers continuously increasing from year to years. The results of the study on Mr. A.G with sensory perception disorders: auditory hallucinations with the application of art therapy showed that the intervention carried out for 2 days was effective, namely there was a change or decrease in signs and symptoms of sensory perception disorders: auditory hallucinations after art therapy. Conclusion: in this scientific paper, there is a decrease in signs and symptoms in Mr. A.G. sensory perception disorders: auditory hallucinations after the application of art therapy. Suggestion: to all health workers to be able to provide education and apply art therapy as one of the actions for patients with sensory perception disorders: auditory hallucination.